Investigating The Shear Behaviour of Hard Points on Honeycomb Sandwich Panels / Nazarrudin Abdullah Ramdzam and Jamaluddin Mahmud - Abdullah Ramdzam, Nazarrudin; Mahmud, Jamaluddin (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Honeycomb sandwich panels which act as the main structure of UiTM solar car, namely Stingray, are exposed to the localize load due to the weight of the handling system components attached to it. Therefore, hard points were introduced to strengthen the structure. Nevertheless, studies pertaining to the shear behaviour of hard points have not been well established. Therefore, this study was aimed to investigate the shear behaviour of hard points on honeycomb sandwich panels due to variations of potting agent volume. The samples, which are panels with hard points were fabricated with variations of potting agent volume (1ml, 2ml and 3ml). Apart from that, panels with hard points made of commercial metal insert (NAS1834) were also fabricated for benchmarking purposes. Shear tests were conducted on the samples to observe the failure mode, where the procedure was based on a published work. Stress-strain diagrams were plotted to determine the Modulus of Rigidity, Gave,1ml, Gave,2ml, Gave,3ml and Gave,NAS1834 and shear strength (the maximum load which the panel could withstand). As an alternative solution, finite element analysis was performed for the same specification. Initially, the panels with hard points were modelled using SOLIDWORKS and then assembled in CATIA. A commercial finite element analysis software, HyperWorks, was used to simulate the deformation behaviour of the panels under shear, according to the conducted tests set up. The experiments results are found to produce similar curves trend to other researchers. The simulated results for shear properties were compared with all the samples from physical tests. In general, the results show that the shear strength of the panels could be increased by increasing the volume of the potting agent. The panels with hard points with 3ml of potting agent volume have the highest shear strength as compared to the other three variations. It can be concluded that the research related to the application of the hard points on the solar car is important and found to be very useful for improving the next UiTM Eco-Photon solar car.